Examining the Evolution of the Field of Public Administration through a Bibliometric Analysis of Public Administration Review. - Ni, Chaoqun; Sugimoto, Cassidy R.; Robbin, Alice (Public Administration Review)
In 2015, Public Administration Review celebrated its 75th year of publication. For this milestone, the PAR Editorial Board selected the 75 most influential articles in the history of the journal and invited scholars to 'revisit a selection of these articles' in order 'to take stock of what these articles meant for the field.' Bibliometrics offers a complementary view of the history of a discipline and the evolution of its research and practice agendas through an analysis of its published literature. This article examines the changes over time in PAR from 1940 through 2013 in authorship: contributions, impact, gender composition, institutional and national affiliation, profession as scholar or practitioner, collaboration networks, and the status of the 75 influential articles. Through an extensive quantitative analysis of scholarly production, this article demonstrates PAR' s centrality to the discipline of public administration and its bridging role between public administration and political science.